Effects of a Cognitive Training With and Without Additional Physical Activity in Healthy Older Adults: A Follow-Up 1 Year After a Randomized Controlled Trial - Kalbe, Elke; Roheger, Mandy; Paluszak, Kay; Meyer, Julia; Becker, Jutta; Fink, Gereon R.; Kukolja, Juraj; Rahn, Andreas; Szabados, Florian; Wirth, Brunhilde; Kessler, Josef (Frontiers in Aging Neuroscience, 2018)
Background: Combining cognitive training (CT) with physical activity (CPT) has been suggested to be most effective in maintaining cognition in healthy older adults, but data are scarce and inconsistent regarding long-term effects (follow-up; FU) and predictors of success. Objective: To investigate the one-year FU effects of CPT versus CT and CPT plus counselling (CPT+C), and to identify predictors for CPT success at FU. Setting and Participants: We included 55 healthy older participants in the data analyses; 18 participants (CPT group) were used for the predictor analysis. Interventions: In a randomized controlled trial, participants conducted a CT, CPT, or CPT+C for seven weeks. Outcome Measures: Overall cognition, verbal, figural, and working memory, verbal fluency, attention, planning, and visuo-construction. Results: While within-group comparisons showed cognitive improvements for all types of training, only one significant interaction Group x Time favoring CPT in comparison to CPT+C was found for overall cognition and verbal long-term memory. The most consistent predictor for CPT success (in verbal short-term memory, verbal fluency, attention) was an initial low baseline performance. Lower education predicted working memory gains. Higher levels of insulin-like growth factor 1 (IGF-1) and lower levels of brain-derived neurotrophic factor at baseline (BDNF) predicted alternating letter verbal fluency gains. Discussion: Within-group comparisons indicate that all used training types are helpful to maintain cognition. The fact that cognitive and sociodemographic data as well as nerve growth factors predict long-term benefits of CPT contributes to the understanding of the mechanisms underlying training success and may ultimately help to adapt training to individual profiles.